Anthropometric record cards used at Family Health Support Centers: What should be measured and why? - Marcius de Almeida Gomes; Carmem Cristina Beck; Maria de Fátima da Silva Duarte; Edio Luiz Petroski (Universidade Federal de Santa Catarina, 2009)
Anthropometry is an important instrument for implementing professional practices in the public health care. In view of the participation of physical education teachers at Family Health Support Centers, the use of anthropometric methods becomes necessary in order to increase its contribution to health-care initiatives. Therefore, this study aims at proposing the application of anthropometry at Family Health Support Centers, indicating procedures for the public health-care environment and considering the principles used for health promotion in Brazil. Besides detecting health risk factors, the application of anthropometry should highlight health-care promotion strategies, so that it allows the involved professionals to mediate control and preventive measures through effective health-care education.